Assessment of fertilizer quality in horse waste-based bokashi fertilizer formulations - Garba Gashua, Auwalu; Sulaiman, Zulkefly; Mohammad Yusoff, Martini; Abd Samad, Mohd Yusoff; Ramlan, Mohd Fauzi; Salisu, Monsuru Adekunle (MDPI, 2022)
Agricultural waste is a type of solid waste that needs to be managed properly. Organic waste can be recycled to produce bokashi fertilizer, which can be used to improve soil health, increase crop production, and sanitize the environment. However, it may contain heavy metals that could be toxic to plants and can pollute the environment if not properly decomposed. This study was designed to evaluate the fertilizer quality of six different bokashi fertilizer ratios (bfrs) over seven- and thirty-day maturation periods. The raw materials used include horse bedding waste (HBW), cow dung (CD), and paddy husk charcoal (PHC) in different ratios, treated with an effective microorganisms (EM4) solution. All the nutrients studied (N, P, K, Mg, and Ca) were significantly affected by the bokashi fertilizer ratios (bfrs). The best bokashi fertilizer ratio was bokashi fertilizer ratio-6 (bfr6), but it was statistically similar to bokashi fertilizer ratio-5 (bfr5). Its N, P, K, Mg, and Ca contents were higher than the control (bfr1) by 133.9%, 225.5%, 196.4%, 105.0%, and 84.7%, respectively. Similarly, all these nutrients were significantly affected by time. N, P, K, and Mg increased by 21.2, 33.0%, 16.4%, and 28.8%, respectively, after 30 days of maturation, with a decrease in Ca only 2.4%, which was not significant A germination index (GI) of 90.1% was obtained using cabbage seeds. The heavy metals result and germination bioassay confirmed the safety and maturity of the bokashi fertilizer. In conclusion, the results revealed that good-quality bokashi fertilizer can be produced within 30 days. Bfrr5 and bfr6 are equally good candidates for producing good-quality bokashi fertilizer for effective crop growth.